(untitled) (International Journal of Engineering and Computer Science, 2021)
Ever since the concept of Fibonacci sequence came in to existence, people tried to generalize it in as many ways as possible. This paper considers one such generalization related to sequences of metallic ratios constructed through number triangles. Interestingly enough, such number triangles provides various amusing properties which will be discussed in this paper.